Konformitas dan Anonimitas Terhadap Ujaran Kebencian dalam Fandom BL Thailand di Twitter - Fakhri, Nurfitriany; Kusuma, Perdana; Kautsariah, Nabila Al (HUMAN: South Asian Journal of Social Studies, 2024)
Abstract. Conformity behavior is closely related to fandom, especially on social media which faces the issue of spreading hate speech through anonymous accounts. This research investigates hate speech among Twitter users who are members of the Thai Boys Love (BL) fan community. Social media, especially Twitter, often becomes a forum for communication between fans and can trigger hate speech behavior. This study involved 156 active members of the Thai BL fandom community on Twitter and used a scale of conformity, anonymity, and verbal aggression. Data analysis using multiple linear regression. The results of the analysis obtained a value of p = 0.000 and r = 0.271. The p value <0.05, so that conformity and anonymity have an influence on the hate test. The value of r indicates a positive correlation direction, which means that the higher the conformity and anonymity, the higher the hate speech in the Thai BL fandom on Twitter. The implications of this research include developing strategies to prevent and deal with hate speech in online communities, especially among fans of Thai BL content on Twitter. Keywords: Anonymity, BL Fandom, Conformity, Hate Speech